Ovarian Pregnancy- A Rare Case Report (Anwer Khan Modern Medical College Journal, 2019)
Ovarian pregnancy is a rare form of the non-tubal ectopic pregnancy. Primary ovarian ectopic pregnancy means  implantation of the gestational sac in the ovary. Its incidence after natural conception ranges from 1 in 2000 to 1  in 60 000 deliveries and accounts for 3% of all ectopic pregnancies. It ends with rupture before the end of the  first trimester. The preoperative diagnosis of this type of pregnancy is not easy. It is characterized by a poor  clinical symptomatology and a difficult ultrasound diagnosis but confirmed by histological findings. For the  management, Conservative laparoscopic surgery involves ovarian resection or aspiration of the pregnancy with  coagulation of the implantation site. However, in case with profuse intraperitoneal bleeding an oophorectomy or  salpingo-oophorectomy may be necessary to achieve hemostasis. We report here one such uncommon case of  ovarian ectopic pregnancy. Our patient is a 27 years old nulliparous woman came with severe hypogastric pain.  During laparoscopy, ruptured ovarian ectopic pregnancy was diagnosed, and wedge resection of the ovary was only done. Histopathological examination confirmed it to be an ovarian ectopic pregnancy.Anwer Khan Modern Medical College Journal Vol. 10, No. 2: July 2019, P 183-185